A Pilot Study of Allogeneic Hematopoietic Stem Cell Transplantation for Intermediated-risk Acute Myeloid Leukemia Patients - OH, MI JIN (In Vivo, 2021)
Background/Aim: Background/Aim: For intermediate risk acute myeloid leukemia patients, allogeneic hematopoietic stem cell transplantation (alloSCT) and chemotherapy are equally recommended as consolidation after first complete remission (CR1). In real-world, alloSCT might not be readily available, but there is paucity of data on the optimal timing of alloSCT for these patients. Patients and Methods: In this pilot study, we compared the outcomes of 13 patients undergoing alloSCT in CR1 with 13 patients undergoing alloSCT after relapse (non-CR1) to examine whether upfront alloSCT yields a better prognosis. Results: There were no differences between the two groups with regards to relapse-free survival (p=0.507) and overall survival (p=0.798). There were more chronic graft-versus-host-disease (GVHD) in the CR1 group compared to the non-CR group (p=0.001), but no difference in acute GVHD. Conclusion: The outcome of alloSCT after relapse is not inferior to that of alloSCT in CR1, supporting the role of alloSCT after relapse in the setting of limited donors and resources